Básník Petr Hruška – marginálie - Urbanová, Svatava (Komisja Slawistyczna PAN, Oddział w Poznaniu, IFS UAM, Wydawnictwo PRO, 2014)
This study presents the work of the Ostrava poet Petr Hruška (1964), one of the most remarkable figures of the middle generation, the poetry of which is of interest due to its authentic message, poetic contemplations and sincere account of its relationship to life. Hruška’s poetry is marked by unity, focus and economy. It deals with both perceptions of the world as well as the spiritual sphere of life. It is marked by established toposes of places (industrial Ostrava), along with the intimacy and individualization of poetic gestures. The poet’s internal line of development is in evidence in his five collections of poetry entitled Obývací nepokoje (Unrest Rooms; 1995), Měsíce (Months; 1998), Vűdycky se ty dveře zavíraly (The Door Had Always Been Closing; 2002), Auta vjíűdějí do lodí (Cars Drive Into Ships; 2007), Darmata (2001) and in the compilation publication of his first three collections entitled Zelený svetr (The Green Sweater), expanded with the part Odstavce (Paragraphs). His reflections range from internal, intimate questions concerning family, full of tension and small family conflicts to man’s relationship to the natural world and the landscape. The collection Darmata, awarded the State Prize for Literature 2013, deals with the confusions of life, with changes in communication and with the relativizing of the impact and value of words. He expresses critical views without denying, however, his own imperfections.
Keywords: contemporary Czech poetry; Ostrava poet of the middle generation; poetic objectivity; time-space and existential dimension